Molecular Systematics of Nocturnal Pollinators (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2022)
Nocturnal pollinators — primarily moths (Lepidoptera: Sphingidae, Noctuidae, Geometridae), hawkmoths, and to a lesser extent beetles and flies — contribute substantially to the pollination of flowering plant communities, yet their taxonomic diversity and phylogenetic relationships remain incompletely resolved compared to diurnal pollinators such as bees andbutterflies. This study employed molecular systematics approaches — including COI DNA barcoding, multi-locusphylogenetic reconstruction (COI, 16S, EF-1α, wingless), and ancestral state reconstruction — to investigate species boundaries, phylogenetic relationships, and the evolutionary origins of nocturnality and floral specialisation in 184 nocturnal pollinator species sampled from 21 European and North African sites. COI barcoding resolved 178 of 184 species (96.7%) with barcode gap analysis confirming species-level identifications; six morphospecies were split into twocryptic lineages each. Maximum-likelihood and Bayesian phylogenies from the four-locus supermatrix (3,284 bp)recovered strongly supported topologies (bootstrap ≥ 75; posterior probability ≥ 0.95 for 94% of nodes) broadlyconcordant with morphological classifications but revealing 14 cases of non-monophyly in currently recognised genera. Ancestral state reconstruction using BayesTraits identified nocturnality as the ancestral condition in Sphingidae with a single secondary reversal to diurnality in the clade containing Macroglossum and Hemaris, and documented 8 independent origins of white/pale floral colour preference — a trait associated with nocturnal pollination syndrome — across the study taxa. Molecular divergence dating placed the major Sphingidae family radiation in the Eocene (42–34 Ma), with European hawkmoth diversification concentrated in the Miocene (18–8 Ma). These results provide a robustmolecular systematic framework for nocturnal pollinator diversity assessment and identify six pairs of previouslyunrecognised cryptic species requiring formal taxonomic description.